(3QbGHI GdbVGA GdEOGQj GdCQOfj Ydi eeGQSI GdehXa GdYGe dMbhbg hMQjGJg GdSjGSjI(B:s (3OQGSI ebGQfI eY GdbGfhfjf GdaQfSj h GdeUQj(B/s - (3SeGg`Q eMeO YHO GdMejO CH`h Qe``Gfs; (3LGHQ LGO fUGQs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B:s (3cdjI GdMbhb (B-(3LGeYI GdbGgQI ,s, 2023)
(3JJejR GdOhdI GdMOjKI (B-(3Gdjhe(B- (3HEROjGO eSDhdjGJgG hJYOO GdJRGeGJgG(B, (3hjQLY GdSHH aj Pdc Edi GJSGY fTGW GdEOGQI djTed ejGOjf eJfhYI GbJUGOjI hGLJeGYjI de Jcf JeGQSgG ef bHd, hfJjLI dgPG GdJhSY agj JMJGL Edi YOO cHjQ ef GdehXajf jYedhf Ydi JSjjQ Yed GdeQGab GdYGeI(B, (3hceG fYde aGdehXa GdYGe jYJHQ GddHfI GdCSGSjI aj HfGA GdOhd(B, (3hjYhO dg GdaVd aj EQSGA bhGYO GdhXjaI GdYGeI(B, (3chfge GdCefGA Ydi GdeUdMI GdYGeI(B, (3hjNVY cd ef GdEOGQI hGdehXajf deHOC GdeTQhYjI aj JSjjQ GdeQab GdYGe(B. (3hjYO hLhO eHOC GdeTQhYjI GdbGfhfjI ef Cge ehVhYGJ GdbGfhf GdYGe, hGdJTQjYGJ GdeJYdbI HGdMbhb hGdMQjGJ GdYGeI, hGdfUhU GdOSJhQjI hGdEOGQjI GdefXeI dgG, aGdSdWI GdJfajPjI hgj echfg ef eLehYI ef GdehXajf jJbjOhf HhGLHGJ, hjeJGRhf HMbhb hMQjGJ NGUg cadgG dge GdOSJhQ, hYdjgG YfO bjGege HegGege aj NOeI GdeQab GdYGe hJSjjQ Yedg HEfJXGe hEWQGO(B, (3cGf dRGkeG Ydjge Cf jJeSchG HhUagG SdWI YGeI, hjJeSc ehXahgG GdYeheejhf HhUage GdeeKdjf ddEOGQI HeHOC GdeTQhYjI GdbGfhfjI, hGMJQGe GdJTQjYGJ GdefXeI ddMbhb hGdhGLHGJ hGdeRGjG hGdbjhO Ydi MmO ShGA(B. s
(3JJejR GdOhdI GdMOjKI (B-(3Gdjhe(B- (3HEROjGO eSDhdjGJgG hJYOO GdJRGeGJgG(B, (3hjQLY GdSHH aj Pdc Edi GJSGY fTGW GdEOGQI djTed ejGOjf eJfhYI GbJUGOjI hGLJeGYjI de Jcf JeGQSgG ef bHd, hfJjLI dgPG GdJhSY agj JMJGL Edi YOO cHjQ ef GdehXajf jYedhf Ydi JSjjQ Yed GdeQGab GdYGeI(B, (3hceG fYde aGdehXa GdYGe jYJHQ GddHfI GdCSGSjI aj HfGA GdOhd(B, (3hjYhO dg GdaVd aj EQSGA bhGYO GdhXjaI GdYGeI(B, (3chfge GdCefGA Ydi GdeUdMI GdYGeI(B, (3hjNVY cd ef GdEOGQI hGdehXajf deHOC GdeTQhYjI aj JSjjQ GdeQab GdYGe(B. (3hjYO hLhO eHOC GdeTQhYjI GdbGfhfjI ef Cge ehVhYGJ GdbGfhf GdYGe, hGdJTQjYGJ GdeJYdbI HGdMbhb hGdMQjGJ GdYGeI, hGdfUhU GdOSJhQjI hGdEOGQjI GdefXeI dgG, aGdSdWI GdJfajPjI hgj echfg ef eLehYI ef GdehXajf jJbjOhf HhGLHGJ, hjeJGRhf HMbhb hMQjGJ NGUg cadgG dge GdOSJhQ, hYdjgG YfO bjGege HegGege aj NOeI GdeQab GdYGe hJSjjQ Yedg HEfJXGe hEWQGO(B, (3cGf dRGkeG Ydjge Cf jJeSchG HhUagG SdWI YGeI, hjJeSc ehXahgG GdYeheejhf HhUage GdeeKdjf ddEOGQI HeHOC GdeTQhYjI GdbGfhfjI, hGMJQGe GdJTQjYGJ GdefXeI ddMbhb hGdhGLHGJ hGdeRGjG hGdbjhO Ydi MmO ShGA(B. s
. (3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI, cdjI GdMbhb, bSe GdbGfhf GdYGe (B2023. s
(3HHdjhLQGajG(B: (3UaMGJ (B220-240.s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbVGA GdGOGQis -- (3GdGQOfs; (3GdeUdMI GdYGeI s -- (3GdSdWI GdJfajPjI s -- (3GdeTQhYjI GdbGfhfjIs -- (3GdehXajf s; (3QSGFd LGeYjI s -- (3LGeYI GdbGgQIs -- (3cdjI GdMbhbs